Bee Venom (Apis Mellifera) an Effective Potential Alternative to Gentamicin for Specific Bacteria Strains Bee Venom an Effective Potential for Bacteria - Hossein Zolfagharian (Journal of Pharmacopuncture, 2016)
Objectives: Mellitine, a major component of bee venom (BV, Apis mellifera), is more active against gram positive than gram negative bacteria. Moreover, BV has been reported to have multiple effects, including antibacterial, antivirus, and anti-inflammation effects, in various types of cells. In addition, wasp venom has bee